2015
DOI: 10.1017/ice.2014.14
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster of Central Line–Associated Bloodstream Infections Due to Rapidly Growing Nontuberculous Mycobacteria in Patients with Hematologic Disorders at a Japanese Tertiary Care Center: An Outbreak Investigation and Review of the Literature

Abstract: BACKGROUND Rapidly growing nontuberculous mycobacteria (RGM) are considered rare pathogens, causing central line-associated bloodstream infection. We identified an outbreak of central line-associated bloodstream infection due to RGM at a hematology-oncology ward during a 5-month period. DESIGN Outbreak investigation and literature review. SETTING A Japanese tertiary care center. PATIENTS Adults who were hospitalized at the hematology-oncology ward from October 15, 2011, through February 17, 2012. RESULTS A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 29 publications
0
20
1
Order By: Relevance
“…RGM BSI has been described in mostly immunosuppressed patients, frequently secondary to malignancies and their entailed therapies [23] , [24] , [25] , [26] . Mizusawa et al showed in a small cohort of 17 immunocompetent patients that 94% of patients were persons who inject drugs (PWID), highlighting the role of skin barrier breakdown in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…RGM BSI has been described in mostly immunosuppressed patients, frequently secondary to malignancies and their entailed therapies [23] , [24] , [25] , [26] . Mizusawa et al showed in a small cohort of 17 immunocompetent patients that 94% of patients were persons who inject drugs (PWID), highlighting the role of skin barrier breakdown in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review identified eight previous outbreaks of CLABSI due to RGM [ 4 11 ]. A total of 43 patients were affected; 21 were children.…”
Section: To the Editormentioning
confidence: 99%
“…A total of 43 patients were affected; 21 were children. All of these outbreaks occurred on haematology–oncology units and half involved HSCT patients [ 4 , 7 , 8 , 11 ].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterium mucogenicum is a rapid-growing mycobacterium formerly known as a Mycobacterium chelonae –like organism ( 1 , 2 ). M. mucogenicum was commonly implicated in outbreaks of opportunistic infections traced to contaminated water systems ( 3 , 4 ) and contaminated hospital equipment ( 5 7 ). Catheter-related infections are the major form of M. mucogenicum opportunistic infection ( 8 , 9 ), and M. mucogenicum is the leading mycobacterium to cause catheter-related bloodstream infections ( 9 ).…”
Section: Genome Announcementmentioning
confidence: 99%